Changes of five tannin compounds in the T. chebula juice at different storage temperatures - Xueyan Li; Lijun Zhang; Jianxing Gu; Fangfang Chen; Yidan Fan; Yuan Fan; Zhusheng Tang (Cogent Food & Agriculture)
To study the effect of different storage temperatures (5, 20, and 35 °C) on the content of five tannins in the Terminalia chebula juice (T. chebula juice). This paper determined five components simultaneously using HPLC, and pH and colour changes were measured. The results showed that the pH value of the T. chebula juice decreased with time under all three storage temperature conditions, with the smoothest variation at 5 °C. The contents of Gallic acid (GA), Epigallocatechin gallate (EGCG), Chebulinic acid (Cl), Chebulagic acid (CA), and Ellagic acid (EA) varied most smoothly at 5 °C. The color of the T. chebula juice did not vary significantly at 5 °C, whereas it varied significantly at 35 °C. The low-temperature preservation of the T. chebula juice can maintain the stability of its physical properties and compounds, which provides a certain reference basis for the production and processing of the T. chebula juice.